A Comprehensive Review of Non-Energy-Based Treatments for Atrophic Acne Scarring - Tam C; Khong J; Tam K; Vasilev R; Wu W; Hazany S (Dove Medical Press, 2022)
Curtis Tam,1 Jeffrey Khong,1 Kevin Tam,1 Ruslan Vasilev,1 Wesley Wu,2 Salar Hazany1 1Salar Hazany M.D. Inc, Beverly Hills, CA, USA; 2Department of Dermatology, Veterans Affairs Medical Center, Seattle, WA, USACorrespondence: Curtis Tam, Salar Hazany M.D. Inc, Beverly Hills, CA, USA, Tel +1 310 571 8435, Fax +1 855 569 5698, Email drsalar@hazanyderm.comAbstract: Scarring is a dire consequence of acne vulgaris. Particularly, atrophic acne scarring is highly prevalent among young adults, and its physical and psychological effects can persist throughout their lives if left untreated. This literature review will analyze various non-energy-based approaches to treating atrophic acne scarring, emphasizing recent advances within the last 5 to 10 years. To accomplish this, we performed a PubMed search for various acne scar treatments such as chemical peels, dermabrasion, microdermabrasion, subcision, microneedling, punch techniques, dermal fillers, and thread lifting. Our findings and analysis show that there is no panacean solution to treating atrophic acne scars, which explains the evolving trend towards developing unique combinatorial treatments. Although a fair comparison of each treatment approach is difficult to achieve due to the studies' varying sample sizes, strength of evidence, treatment execution, etc, there still remains a level of consensus on what treatments are well suited for particular scar types.Keywords: TCA, subcision, microdermabrasion, microneedling, fillers, excision